2015
DOI: 10.3923/jps.2015.75.78
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodistillation and Comparative Report of Percentage Yield on Leaves and Fruit Peels from Different Citrus Plants of Rutaceae Family

Abstract: Citrus fruit peels and leaves have always been the imperative attention of different researchers in pharmaceutical and cosmeceutical field. Moreover, the aroma of essential oil gains good reputation in aromatherapy. The volatile oil from leaves and rind of the citrus fruit has been reported by Hydrodistillation and expression methods several times. At this time, in present study, extraction of volatile oil forms the leaves and peels of fruit from citrus plants were obtained by hydrodistillation. Total seven Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…1). These results were lower but compared favourably with those obtained for the peel oils of seven citrus species from the Solan district of the Himachal Pradesh state in northern India investigated by Sharma and Vashist (2015). This yields are however slightly higher than those obtained by Kamal, et al (2011) In all, the compounds identified are categorized as hydrocarbon monoterpenoids, oxygenated monoterpenoids, sesquiterpenoids and non-terpenes (Table 2).…”
Section: Results and Discusionmentioning
confidence: 46%
“…1). These results were lower but compared favourably with those obtained for the peel oils of seven citrus species from the Solan district of the Himachal Pradesh state in northern India investigated by Sharma and Vashist (2015). This yields are however slightly higher than those obtained by Kamal, et al (2011) In all, the compounds identified are categorized as hydrocarbon monoterpenoids, oxygenated monoterpenoids, sesquiterpenoids and non-terpenes (Table 2).…”
Section: Results and Discusionmentioning
confidence: 46%
“…In this study, LPO isolation utilized the hydrodistillation method, yielding 0.48 ± 0.014 %. Comparable methods were employed by previous researchers in isolating LPO, yielding 0.21–2.00 % ( Julaeha et al, 2023 , Pratiwi et al, 2022 , Sharma and Vashist, 2015 ). Furthermore, Varkey et al (2013) used hydrodistillation in five different places and obtained essential oils from C. aurantifolia leaves and bark that were between 0.10 and 0.14 % and 0.30 % and 0.60 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of the isolated LO was still marginally consistent with the yield obtained elsewhere (0.2-2%). 19,[33][34][35][36][37] Such a result is reasonable because geographical conditions, climate, season, and maturity of the fruits considerably inuence the LO yield. 38,39 The resulting LO exhibited a distinctive lime scent with a pale-yellow color.…”
Section: Lo Microencapsulation and Characterizationmentioning
confidence: 99%